CHOP-like-14 compared to CHOP-like-21 for patients with aggressive lymphoma – a meta-analysis of randomized controlled trials. (2nd January 2016) - Vidal, Liat; Shpilberg, Ofer; Gurion, Ronit; Monsef, Ina; Raanani, Pia; Ram, Ron; Gafter-Gvili, Anat
Abstract : Background. R-CHOP-21 has remained the standard chemotherapy for aggressive non-Hodgkin's lymphoma. It was suggested that decreasing the treatment interval from three weeks (CHOP-21) to two weeks (CHOP-14) may improve survival and disease control of patients with aggressive lymphoma. Purpose. To evaluate the effect of CHOP-like-14 (with or without rituximab) compared to standard CHOP-like -21 on overall survival (OS), disease control and toxicity of patients with aggressive non-Hodgkin lymphoma. Methods. Systematic review and meta-analysis of RCTs. In October 2014 we searched The Cochrane Library, MEDLINE, LILACS, conference proceedings, and databases of ongoing trials. Authors were contacted for complementary data. The primary outcome was OS. Results. We identified seven trials (4073 patients), conducted between the years 1999 and 2008. Trials were at low or unclear risk for selection bias, and at low or unclear risk of attrition bias. CHOP-like-14 improved OS of patients with aggressive lymphoma compared to the same regimen given every 21 days (all trials): HR of death 0.86, 95% confidence interval (CI) 0.77–0.97. There was no OS difference between rituximab-CHOP-like 14 to rituximab-CHOP-like-21 (3 trials): HR 0.93 95% CI 0.78–1.10. The rates of progression or death, complete response, treatment-related mortality, grade 3–4 infection, and discontinuation were similar between groups. Conclusion. R-CHOP-21 remains the standard of care for patient with aggressive B-cell lymphoma. CHOP-14 can be considered as in case rituximab is omitted.